Use of peers, community lay persons and Village Health Team (VHT) members improves six-week postnatal clinic (PNC) follow-up and Early Infant HIV Diagnosis (EID) in urban and rural health units in Uganda: A one-year implementation study - Namukwaya, Zikulah; Barlow-Mosha, Linda; Mudiope, Peter; Matovu, Joyce Namale; Etima, Juliane; Musoke, Philippa Martha (BMC health services research, 2015)
Effective Prevention of Mother to child Transmission of HIV (PMTCT) relies heavily on follow-up of HIV-infected women and infants from antenatal, through postnatal, to the end of the breastfeeding period. In Uganda, postnatal (PNC) follow-up remains below 50 % creating a missed opportunity for linkage to comprehensive HIV care and early infant diagnosis (EID). We evaluated the use of HIV infected peer mothers (peers), community lay persons and Village health team (VHT) members to improve PNC follow up and EID in urban and rural health units.